The Correlation between the use of the SBAR Effective Communication Method and the Handover Implementation of Nurses on Patient Safety - Dewi Mulfiyanti; Andi Satriana (International Journal of Public Health Excellence (IJPHE), 2022)
Background: Patient safety is a system implemented in hospitals with the aim of providing patient comfort in the treatment process. One of the effective communication methods is using the Situation Background Assessment Recommendation (SBAR) approach, this communication method is used when nurses carry out handovers to achieve critical thinking skills and save time during the treatment process. The SBAR approach has proven to be an effective communication tool in acute and urgent patient care settings. This review aims to find effective communication methods to reduce or reduce the number of patient safety incidents, improve service quality and improve the quality of nursing care. Purpose: To find out the relationship between the use of the SBAR effective communication method and the implementation of handovers on patient safety. Methods: Using a Literature review research design with the journal search method using the Google Scholar and Elsevier databases. Results: Researchers found 13 articles that met the inclusion and exclusion criteria. The results of the literature review show that effective communication using the SBAR approach can reduce errors in communication between health workers and health workers with patients so as to prevent unwanted events. Therefore, effective communication with the SBAR approach can also improve the quality of hospital services and increase patient satisfaction and effective SBAR communication plays an important role in the implementation of handover of patient safety. Conclusion: The results of a systematic literature review show that there is a relationship between the use of the effective SBAR communication method and the implementation of handovers on patient safety and the effective communication method with the SBAR approach is expected to become a communication method that can improve service quality, reduce patient safety incidents and prevent the occurrence of unwanted events, and can affect patient satisfaction and nurse loyalty.